PENGARUH PEMBERIAN IMUNOMODULATOR JINTAN HITAM (Nigella sativa L.) DI DALAM AIR MINUM TERHADAP TITTER ANTIBODI AVIAN INFLUENZA (AI) DAN NEWCASTLE DISEASE (ND) PADA BROILER BETINA - Neni Kikiyani, Siswanto, Purnama Edy Santosa, dan Madi Hartono (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2020)
The aim of this research was to know the effectiveness of Nigella sativa L. as an immunomodulator given in drinking water with different doses on AI and ND antibody titers in female broilers. This research was conducted in December 2019 -- January 2020 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The antibody titers was analyzed at the Lampung Veteriner Virology Laboratory in Lampung. This study used a Completely Randomized Design (CRD) with four treatments and three replications; namely drinking water without Nigella sativa L. (control) (P0), drinking water with 36 mg/kg BW/day Nigella sativa L., drinking water with 72 mg/kg BW/day Nigella sativa L., and drinking water with 144 mg/kg BW/day Nigella sativa L. The antibody titer data from each treatment and control was arranged in the form of a histogram and simple tabulations and then were analyzed descriptively. The results of this study indicated that female broilers given Nigella sativa L. was effective in increasing Newcastle Disease antibody titers and was not effective in increasing Avian Influenza antibody titers in female broilers. Giving Nigella sativa L. As much as 36 mg/kg BW/day in drinking water could increase the Newcastle Disease antibody titer in female broilers. Keywords: Antibody titer, Avian Influenza, Female broilers, Immunomodulator, Newcastle Disease, Nigella sativa L.